Separation of powers and the institutional supremacy of the Constitutional Court over Parliament and the executive. Issue 4 (1st October 2020) - Dube, Felix
Abstract: South African judges often caution against judicial encroachment into what they perceive as the exclusive domains of the legislature and the executive. Their caveats stem from the doctrine of separation of powers, which classically divides state authority between the three branches of government. However, the classification of the courts, particularly the Constitutional Court, as a branch of the government potentially misconstrues the division of state authority in the Constitution of the Republic of South Africa, 1996. The powers and authority of the Constitutional Court place it at the apex of the legal and political order such that from a conceptual and practical view, the Court is constitutionally superior to Parliament and the executive. As such, a traditional understanding of the doctrine of separation of powers does not properly reflect the South African constitutional arrangement. This contribution re-evaluates the relevance and application of the doctrine of separation of powers in contemporary jurisprudence. It recognises the superiority of the Constitutional Court over Parliament and the executive and shows that the time has come to consider the institutional supremacy of the Constitutional Court as a possible doctrine of constitutional law in South Africa.